PRODUCTIVITY AND QUALITY: A STRATEGY FOR THE SA DEFENCE FORCE - Eberlein, R. (Scientia Militaria - South African Journal of Military Studies, 2012)
In recent times the SA Defence Force (SADF) has been bombarded with a variety of methods and approaches to the improvement of productivity, financial savings and, most recently, for quality of work life or quality assurance. Various approaches have included the concepts of Total Quality Management (TQM), Quality Circles (and variants in the guise of Triads and others), Methodology, Unit Management Systems, Cost Control Systems, Deterministic Productivity Accounting and the Iike. There have been many benefits to be found in these various approaches, each of which concentrates on certain aspects of productivity. That there have been great achievements in productivity in the SADF is a matter of record, a record which is reflected in a National Award for Productivity, a smaller more efficient SADF, and a reputation for submitting more recommendations for improvements than other departments in the Public Service. At a more personal level though, the writer has gained the impression that no or very little attempt has been made to integrate selected aspects of these approaches into an overall "productivity” strategy acceptable to the SADF. That there is a need for such an overall strategy is clear from the sentiments expressed recently by the members of the SADF’s Productivity Co-ordination Committee when attempting to indicate the way ahead to even greater productivity in the SADF (Meeting, January 1991). In this paper a strategy for the improvement of productivity and the quality of work life which is acceptable to the SADF is proposed.